INSTALLATION IN THE POST-INTERNET ERA / ИНСТАЛЛЯЦИЯ В ЭПОХУ ПОСТИНТЕРНЕТА - BOKHOROV KONSTANTIN Y. / БОХОРОВ К.Ю. (Наука телевидения, 2019)
In contemporary culture installation has become the leading genre of artistic creativity. In connection with this the question of criterial base for its evaluation becomes an essential one. In this article it is examined on the basis of a methodology suggested by cultural theoretician Boris Groys, who criticizes the “realism” of installation-based art which characterizes the presentation of results of its thematic research by artists who use open sources of information, including the internet, from the positions of the symbolic context of museum representation. The “museum” in the broad sense of the word plays the role of the symbolic replacement of the universal government which endowed a sovereign status to art in contemporary culture. Thereby, installation must not simply represent in a most accessible manner certain information in a spatially unfolded form, but to problematize the very structure of representation as a derivative of global historical transformation. The art characterized by the conception of “post-internet,” is particularly the type of such installation-based solution. The article examines in detail the installations of German artist Hito Steyerl within the framework of the Muenster Sculptural Project of 2016. It fits in the institution representing it into the global context of modernity, indicating the semantic split of its cultural and economic connections. For this reason, although Steyerl’s installation is not characterized highly technological solutions, plastic unity, or a connected narrative of the presented material, it may be considered a specimen of a successful artistic manifestation of this genre. The work of the artists of the post-internet is juxtaposed in the article to what is done by artists and media-theoreticians who make use of new technologies for the creation of spectacular media products directed at engaging the viewer into play with highly technological contemporaneity. In particular, Lev Manovich’s project “On Broadway” from the years 2014-2016 is examined. Attention is drawn to the fact that notwithstanding all the technological perfection of this installation-based product and its spatial-plastic expressivity, it simplifies the perception of the space into which the universal artistic institution is fit in, and thereby brings discredit to it in reality. Thereby, the methodology of Groys makes it possible to describe and critically evaluate various types of installations laying claim to the status of art in contemporary artistic culture.